Kompetensi SDM dan Kualitas Pelayanan Rumah Sakit - Ratnamiasih, Ina; Govindaraju, Rajesri; Prihartono, Budhi; Sudirman, Iman (Jurnal Trikonomika, 2012)
There are many studies about factors influencing the hospital service quality. Theyâre focused on those aspects of the services directly felt by the patient. Problems that cause the low service quality had been studying, continually. In this preliminary study, factors influencing the service quality that are related to clinical human resources competency are explored. Factors that mediate the relationship between human resource competency and service quality, namely job satisfaction, also discussed in this study so as to obtain a comprehensive picture of the factors that cause the service quality. This study is an exploratory study. A single case study was executed at a private hospital in Bandung. A number of semi-structured interviews were executed with a number of doctors, hospital managers and nurses. Questionnaires were distributed to a number of nurses. The results showed that the the clinical human resource competency influences the hospital service quality through job satisfaction.